The Seeking Treatment among Breast Cancer Patients - Febrianti, Thresya; Masjkuri, Nuning M. K. (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2016)
Background: Breast cancer is the second highest-rate incidence after cervical cancer. Moreover, the breast cancer epidemic is getting increasing over years. The aim of this research was to know the strength correlation between knowledge and delay in seeking treatment among breast cancer patients at General Hospital Center Dr. M. Djamil Padang. Method: This was a case control study. Respondents of the research were patients of breast cancer and had been registered at General Hospital Center Dr. M. Djamil Padang in July-December 2013. 122 of the total sample dividedÂ  61 cases and 61 controls were collected. Results: This research showed level of knowledge of controlled women had 1.86 times the odds of delay in seeking treatment of breast cancer. (OR=1.86, 95% CI 0.68 to 5.089). Therefore, having higher awareness in breast cancer is driven womenÂ  to early detection and screening methods by conducting an intensive counseling. Conclussion: Women had lower knowledge of breast cancer treatment this analysis suggests that women need further information about the different types of breast cancer symptoms to assist symptom recognition